Verification 1996 arms control, peacekeeping, and the environment - Poole, J. B; Guthrie, Richard (Verification Technology Information Centre : Westview Press, 1996)
This is the sixth volume in a series of annual reviews of the implementation of arms control and environmental agreements and of peacekeeping activities. Documenting developments in the field during 1995, including the indefinite extension of the Non-Proliferation Treaty, this collection of essays discusses challenges for 1996: negotiation of a comprehensive test ban; potential difficulties facing the Dayton Agreement; the evolving role and functions of NATO; continuing ethnic conflict in Russia; and slow progress toward agreements protecting the environment, among other issues.